Taking hobbyists seriously: The reef tank hobby and knowledge production in serious leisure. (June 2022) - Muka, Samantha
Abstract: Studies of communities that produce knowledge about the natural world have largely focused on groups working with or for academic scientists and conforming to the epistemic values of academic knowledge production. This paper details a community that produces natural knowledge outside of those parameters. The reef hobbyist community, a group that works with aquariums as a form of non-professional leisure, has developed historical narratives, publishing standards, and recognized forms of expertise that are not shared by academic scientists. However, their goal is to produce knowledge about coral systems and their hobby has resulted in a wealth of knowledge about coral husbandry. In this paper, I identify the structure of this community, highlight several prominent groups that make up the network of reef hobbyists, and trace the ways that they produce knowledge about the marine environment through their actions. This paper contributes to discussions about diverse ways of knowing and differing forms of knowledge production in the history and philosophy of science. By examining the history and practices of a well-developed knowledge community outside of academic science, I hope to call attention to the ways that philosophers and historians have centered academic science and its structure and use of knowledge, even in conversations about non-professional knowledge producers. This paper pushes scholars to think more deeply about the way knowledge is developed in non-academic groups.